B429 An audit of single shot regional techniques in paediatric patients at a tertiary orthopaedic hospital. (11th August 2022) - Dsouza, SL; Cooper, M
Abstract : Background and Aims: Regional anaesthesia (RA) with a GA in paediatrics results in superior analgesia, reduced opioid usage and earlier discharge . 1, 2 At our hospital, we have a sizeable paediatric surgical population and RA is frequently used. This audit was triggered by 2 complaints about transitional analgesia following RA on the paediatric ward. Aims: Define patient cohort and assess efficacy of analgesic techniques. Assess if there is a hidden problem of inadequate transitional analgesia following RA Suggest an approach for managing transitional analgesia Methods: After ethics commitee approval, a retrospective audit was done to assess the analgesic requirements after RA co-anaesthesia techniques in paediatric patients. Type of surgery/RA, intraoperative and postoperative analgesic requirements, recovery pain scores, time to 1st opioid and 24 hour opioid requirements, highest pain score on the ward and pain score on discharge were recorded. Patients sent to PACU or needing a PCA were excluded. Results: 31 female and 29 male children varying from 6 months -17 years operated from Jan to June 2020 were included. Recovery, ward and discharge pain scores were higher and time to first rescue opioid was shorter in popliteal and caudal blocks and surgeries on lower leg and ankle. Conclusions: Children undergoing lower leg/ankle surgeries with popliteal/caudal blocks could benefit from targeted postoperative analgesia. This group can be the one to trial timed immediate release (IR) opioid doses (6 hours postop) and education to ward staff to ensure that they receive it. A high quality low risk team based plan is suggested as below.